Electromagnetic navigation system for computed tomography-guided synchronous percutaneous lung biopsy and microwave ablation of pulmonary nodules: a prospective, single-center, single-arm clinical study - Shengwei Li; Zhixin Bie; Yuanming Li; Jie Sun; Jiangxu Zhang; Xiangyu Zi; Runqi Guo; Xiao-Guang Li (International Journal of Hyperthermia)
Background The purpose of this study was to clinically evaluate the safety and effectiveness of the electromagnetic navigation (EMN) system designed for computed tomography (CT)-guided synchronous percutaneous lung biopsy and microwave ablation (MWA) of pulmonary nodules.Methods This prospective, single-center, single-arm clinical cohort study was conducted in Beijing Hospital from March 2023 to May 2023. Patients who underwent CT-guided synchronous percutaneous lung biopsy and MWA via the EMN system were prospectively enrolled in our study. All the interventional procedures were performed by the same interventional radiologist. The technical success rate, the technical efficacy rates of biopsy and MWA were assessed as the primary outcomes. Preoperative, intraoperative, and postoperative variables were also recorded and analyzed for each patient.Results A total of 48 patients were enrolled in the study. The technical success rate was 100%. The technical efficacy rate of biopsy was 95.8% (46/48), and the technical efficacy rate of WMA was 100% (48/48) with no recurrence during follow-up. The total and subpleural needle trajectory length and distance error were 8.3 ± 2.6 cm, 3.6 ± 1.6 cm, and 1.84 ± 1.08 mm, respectively. The median numbers of needle adjustments and CT acquisitions were 1 (range 1–3) and 3 (range 3–5), respectively. The time to reach the target and procedure time were 4.4 ± 1.7 and 19.7 ± 5.2 min, respectively. The dose length product was 748.8 ± 221.8 mGy*cm. The median postoperative hospital stay was 1 (range 1–7) days. No major complications (grade ≥3) occurred and only seven minor complications (14.6%) occurred, including six cases of pneumothorax and one case of hemoptysis. The radiologists achieved high satisfaction scores after surgery.Conclusion The EMN system is feasible, safe and effective for CT-guided synchronous percutaneous lung biopsy and MWA of pulmonary nodules.